Predictors of distress and well‐being in parents of young children with developmental delays and disabilities: the importance of parent perceptions. (28th August 2014) - Minnes, P.; Perry, A.; Weiss, J. A.
Abstract: Background: Moving from family‐centred to child‐centred models of service delivery can be stressful for parents as their young children with developmental delays and disabilities transition into school. The purpose of this paper was to explore and compare predictors of both distress and well‐being in parents during this transition period. Methods: A sample of 155 mothers of 113 boys and 42 girls participated in the study. The mean age of the children was 4.9 years and their diagnoses included autism spectrum disorder (52%); unspecified intellectual disability/developmental delay (26%); Down syndrome (12%); other genetic conditions (4%) and other diagnoses (6%). Participants completed surveys primarily online focusing on child characteristics, family resources, parent coping strategies, parental distress and positive gain. Results: Multiple regression analyses were conducted to determine predictors of parent reported distress and positive gain. Parent coping variables were the strongest predictors of both positive gain and parental distress, with reframing emerging as a predictor of positive gain and parent empowerment emerging as a predictor of both greater positive gain and lower parental distress. Conclusions: The results of this study highlight not only the importance of including positive as well as negative outcomes in research with parents but also the importance of including parent characteristics such as coping strategies (e.g. reframing and empowerment/self‐efficacy) as potential predictors of outcome in such studies.